Studies on aluminium sulphate induced alterations in lipid profile in albino rat - NEELAM UPADHYAY; P.K. SINGH; REENA YADAV (International Journal of Pharma and Bio Sciences, 2019)
This study evaluated the changes in lipid profile after aluminum induced toxicity in wistar rats. Pollutants are heavy metal substances in the environment which cause objects to enable effects, impairing the welfare of environment reducing the quality of life and may eventually cause death. Although heavy metal poisoning could be clinically diagnosed and medically treated, the best option is to prevent heavy metal pollution and the subsequent human poisoning. In the present study, an attempt has been made to evaluate the harmful effects of aluminum on blood lipid profiles to elucidate general health conditions in albino rats and results obtained can be applied to other mammals, including humans. The work has been done as per standard procedures and protocol in departmental laboratory. The results of present study clearly reflects significant alteration in lipid profile that can be considered as mark to show heavy metal toxicity. The outcome of the study showed that aluminum is capable to alter lipid profile parameters in mammals which can seriously affect the health and physiology of the affected animal. It is suggested to minimize the use of aluminum and whenever used, caution should be taken.